Evaluation of Staff Nurses' Proficiency in Safety Measures for specific practices - Mohammed Ibrahim Mohammed Al Tukhays,; Meatap Manea Abdullah Mutair,; Mariam Abdu Sharahili,; Alanoud Miqad Qarrash Alotaibi,; Abdullah Bin Saleh Al-Rashidi,; Abdulmohsen Muidh Jazi Alotaibi,; Khaled Abdullah Shafi Al-Toum,; Khaled Abdulrahman Zwaid Al-Qaddah,; Basma Lubnan Zafir Aldossery,; Shabab mohd said Alzahrani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: In order to reduce nursing errors, nursing competency and practice safety are important issues in clinical practice and nursing education settings. Nursing errors accounted for 25% of sentinel events in the healthcare industry, with the bulk of these errors being caused by healthcare professionals' ineptitude. The study's objective is to evaluate staff nurses' proficiency with safety precautions for particular procedures. Research design: This study employed a descriptive research approach. 233 nurses was accepted to assigned in the research . Setting: East Jaddah Hospital . Data collecting tool: a single tool with two sections: a sociodemographic data sheet in part one and a performance check list in part two. Findings: two-thirds (63.3%) of nurses at East Jaddah Hospital did not follow infection control procedures. there was a statistically significant positive connection (p=0.001) between environmental safety, medicine delivery safety, and infection control competency.also, this study revealed that there is low competency level of staff nurses due to the lack of nursing competency assessment for nurses. Conclusion: this study revealed that there is low competency level of staff nurses, also it is important for integrating a structured nursing competency assessment that measures nursing competence in the nursing care delivery systems and determining the competency levels of nurses to ensure safe nursing practice.